Simplified engineering for architects and builders - Parker, Harry; Ambrose, James (New York : John Wiley & Son, Inc., 1989)
With the publication of this edition of Professor Parker's book, another generation of building designers is afforded the opportunity to utilize the most enduringly popular general reference for study of the topic of design of building structure.
Principles of structural mechanics -- Wood construction -- Steel construction -- Concrete and masonry construction -- Structural system for buildings.
Includes bibliographical references and index.
Keywords: ARCHITECTURE DESIGN, DRAFTING, DRAWING AND PRESENTATION